Attrition of Households and Individuals in Panel Surveys - Oliver Lipps (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Attrition is mostly caused by not contacted or refusing sample members. On one hand it is well-known that reasons to attrite due to non-contact are different from those that are due to refusal. On the other hand does non-contact most probably affect household attrition, while refusal can be effective on both households and individuals. In this article, attrition on both the household and (conditional on household participation) the individual level is analysed in three panel surveys from the Cross National Equivalent File (CNEF): the German Socio- Economic Panel (GSOEP), the British Household Panel Study (BHPS), and the Swiss Household Panel (SHP). To follow households over time we use a common rule in all three surveys. First, we find different attrition magnitudes and patterns both across the surveys and also on the household and the individual level. Second, there is more evidence for reinforced rather than compensated household level selection effects if the individual level is also taken into account.
Keywords: 330; CNEF; individual attrition; household attrition; attrition bias; reference person; household head